1985
DOI: 10.1093/oxfordjournals.aje.a113984
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin a Deficiencies and Stomach Cancer

Abstract: The hypothesis of vitamin A intake deficiencies serving as an antecedent factor in the development of stomach cancer was assessed employing a case-control design. Interviews of proxy informants for 111 cases and a pair-matched control group were conducted using a food frequency questionnaire from which an averaged vitamin A intake index was calculated. Stomach cancer cases showed a significantly higher proportion with lowered total vitamin A intake levels (odds ratio = 1.71) which remained constant across sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 0 publications
2
8
0
1
Order By: Relevance
“…Our findings of a dose-response reduction in risk associated with increases in ingestion of carotene and certain vegetables are consistent with previous observations (25,(31)(32)(33)(34)(35)(36)(37)(38), as shown in Table 11.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings of a dose-response reduction in risk associated with increases in ingestion of carotene and certain vegetables are consistent with previous observations (25,(31)(32)(33)(34)(35)(36)(37)(38), as shown in Table 11.…”
Section: Discussionsupporting
confidence: 93%
“…Also, epidemiological inquiries found increases in risk with salt ingestion, either when studied as total ingestion of sodium in foods or when examined per specific highly salted food item. 32 Nutrition and Cancer 1990…”
Section: Discussionmentioning
confidence: 99%
“…It showed no significant anti-cancer activity. Rettura and his colleagues (1982) found that beta-carotene (and retinyl (Stocks, 1958;Bjelke, 1975;Phillips, 1975;MacLennan et al, 1977;Bjelke, 1978;Tuyns et al, 1978;Cook-Mozaffari et al, 1979;Hirayama, 1979;Mettlin et al, 1979;Gregor et al, 1980;Mettlin et al, 1981;Modan et al, 1981;Shekelle et al, 1981;Kvale et al, 1983;Byers et al, 1984;Hinds et al, 1984;Ziegler et al, 1984;Long-De W. et al, 1985;Samet et al, 1985;Stehr et al, 1985;Wu et al, 1985;Pisani et al, 1986;Kolonel et al, 1987). For lung cancer, the results are clear-cut; the relative risk lying between 1.5 and 2.5 among those with low estimated betacarotene intakes compared with those with a high intake.…”
mentioning
confidence: 99%
“…These include various agents with damaging effects on the normal gastric epithelium, as mentioned in the literature. Helicobacter pylori infection (Taylor & Blaser, 1991;Forman et al, 1994;Nightingale & Grueber, 1994;Munõz, 1994), perhaps mainly during early periods of life (Goodman & Correa, 1995), nitrosamine precursors in industrialized foods (Mirvish, 1994), and facilitating factors associated with either a salt-rich diet, alcohol intake, or deficient consumption of fresh fruits and vegetables have been mentioned as associated with stomach cancer (Antonioli, 1994;Hwang et al, 1994;Kodama et al, 1984;Risch et al, 1985;Stehr et al, 1985).…”
Section: Introductionmentioning
confidence: 99%